Using citizen science data to assess the difference in marine debris loads on reefs in Queensland, Australia. (October 2018) - Bauer-Civiello, Anne; Loder, Jennifer; Hamann, Mark
Abstract: The prevalence of marine debris in global oceans is negatively impacting the marine environment. In Australia, marine debris has been an increasing concern for sensitive marine environments, such as coral reefs. Citizen science can contribute data to explore patterns of subtidal marine debris loads. This study uses data from Reef Check Australia to describe patterns of debris abundance on reef tourism sites in two Queensland regions, the Great Barrier Reef (GBR) and Southeast Queensland (SEQ). Debris was categorized into three groups, fishing line, fishing net, and general rubbish. Overall, debris abundance across reefs was relatively low (average 0.5–3.3 items per survey (400 m 2 )), but not absent on remote reefs surveyed in the GBR region. Highest debris loads were recorded in SEQ near cities and high use areas. These results indicate the presence of marine debris on remote and urban reefs, and the applicability of using citizen science to monitor debris abundance. Highlights: Long term monitoring data from Reef Check Australia was used to determine subtidal debris loads on Queensland reefs. Debris abundance across reefs was relatively low, with an average between 0.5-3.3 items per survey (400m 2 ). Marine debris was more abundant near cities and high use areas, but not absent from remote reefs within the GBR region. Overall, fishing line was the most common debris item, and was most commonly observed in Southeast Queensland.